Radius problems for certain classes of analytic functions - CHUNG, Yao Liang; MOHD, Maisarah Haji; SUPRAMANIAM, Shamani (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
Radius constants for functions in three classes of analytic functions to be a starlike function of order α, parabolic starlike function, starlike function associated with lemniscate of Bernoulli, exponential function, cardioid, sine function, lune, a particular rational function, and reverse lemniscate are obtained. Mathematics Subject Classification (2010): 30C45. Received 29 December 2020; Accepted 23 March 2021. Published Online: 2023-12-11 Published Print: 2023-12-30